Le traitement des établissements de crédit en difficulté en zone CEMAC - Piih, Dieudonné (Sorbonne Paris Cité, 2018)
Depuis 2014, le législateur CEMAC a institué un droit spécifique des défaillances bancaires. Un an plus tard, le législateur OHADA, en réformant le droit commun des procédures collectives, a reconnu le traitement particulier des difficultés bancaires. Le problème de la pertinence de ce régime spécifique nous a amenés à démontrer que la notion de difficulté est le critère principal de sa spécificité. En effet, le droit commun a une conception patrimoniale des difficultés. Elles sont essentiellement économiques ou financières. La cessation de paiements en constitue la notion incontournable. Incontournable en droit commun, elle est une notion à géométrie variable en droit spécifique. Elle n'est plus l'état où l'établissement de crédit se trouve dans l'impossibilité de faire face à son passif exigible avec son actif disponible, mais plutôt lorsqu'il ne peut plus assurer ses paiements immédiatement ou dans un délai de trente jours. Au-delà de cette adaptation de la définition de la cessation de paiements, le législateur CEMAC considère de manière inédite que le retrait d'agrément vaut cessation de paiements. Or, il existe deux procédures de retrait d'agrément, notamment le retrait d'agrément disciplinaire et prudentiel. Ainsi, la cessation de paiements peut être disciplinaire ou prudentielle selon la procédure de retrait d'agrément. Sur le plan processuel, la cessation de paiements n'est pas la condition d'ouverture des procédures collectives en droit CEMAC. En matière de redressement judiciaire, la procédure sera déclenchée par l'avis conforme de la COBAC. En ce qui concerne la liquidation des biens, le retrait d'agrément ouvre d'office la procédure. Aujourd'hui, on n'est en droit de se poser la question de savoir que reste-t-il de la cessation de paiements. En vérité, rien ne reste plus de la cessation de paiements puisque même en définissant un établissement de crédit en difficulté, le législateur CEMAC n'y fait pas référence. Il considère qu'un établissement de crédit est en difficulté lorsque la COBAC constate les dysfonctionnements majeurs de toute nature ayant un impact immédiat ou prévisible sur sa gestion et/ou sa structure financière. Il en résulte que la conception des difficultés en droit CEMAC est plus extensive qu'en droit commun. C'est pourquoi, nous proposons une réforme du droit commun pour une appréciation plus objective de la notion de difficulté, notamment par la notation ou par la classification des créances inspirée de la réglementation bancaire et une extension aux difficultés extra-économique ou financière telles que le retrait d'agrément ou la cessation d'activités. Le problème de la pertinence du régime spécifique conduit également à s'interroger sur les conditions de sa cohabitation avec le droit commun. Il en résulte de manière générale que la COBAC contrôle l'ouverture de la procédure de droit commun, soit par l'autorisation préalable, soit par l'avis conforme, soit par la désignation d'un liquidateur bancaire, une sorte de « janus biface », soit enfin par la scission du patrimoine de l'établissement de crédit en compartiment bancaire et non bancaire. Mieux, la COBAC détient un droit de veto. Aucune procédure collective ne peut être ouverte à l'égard d'un établissement de crédit sous administration provisoire ou sous restructuration. Le droit de contrôle de la COBAC se justifie par le fait qu'elle est dotée des pouvoirs et dispose des mesures plus efficaces, notamment le Fonds de garantie, pour éviter le risque systémique. Since 2014, the CEMAC legislator has instituted a specific right of bank failures. A year later, the OHADA legislator, in reforming the common law of insolvency proceedings, recognized the special treatment of banking difficulties. The problem of the relevance of this specific regime has led us to show that the notion of difficulty is the main criterion of its specificity. Indeed, common law has a patrimonial conception of difficulties. They are essentially economic or financial. The cessation of payments is the essential notion. Incontournable in common law, it is a concept with variable geometry in specific law. It is no longer the state in which the credit institution is unable to meet its due liability with its available assets, but rather when it can no longer provide its payments immediately or within thirty days. Beyond this adaptation of the definition of the cessation of payments, the CEMAC legislator considers in an unprecedented way that the withdrawal of approval constitutes cessation of payments. However, there are two procedures for withdrawal of approval, including the withdrawal of disciplinary and prudential approval. Thus, the cessation of payments can be disciplinary or prudential according to the withdrawal procedure. On a procedural level, the cessation of payments is not the condition for opening collective proceedings in CEMAC law. In judicial redress, the procedure will be triggered by the assent of COBAC. With regard to the liquidation of property, withdrawal of approval automatically opens the procedure. Today, we are not entitled to ask ourselves the question of what remains of the cessation of payments. In truth, nothing remains of the cessation of payments since even by defining a credit institution in difficulty, the legislator CEMAC does not refer to it. It considers that a credit institution is in difficulty when COBAC notices major malfunctions of any kind having an immediate or foreseeable impact on its management and / or its financial structure. As a result, the conception of difficulties in CEMAC law is more extensive than in common law. This is why we propose a reform of the common law for a more objective assessment of the notion of difficulty, notably by the rating or classification of claims inspired by banking regulations and an extension to extra-economic or financial difficulties such as withdrawal of approval or cessation of activities. The problem of the relevance of the specific regime also raises the question of the conditions of its cohabitation with common law. As a general result, COBAC controls the opening of the ordinary law procedure, either by prior authorization, by the assent, or by the appointment of a bank liquidator, a kind of ''janus biface''. '', Or finally by the division of the assets of the credit institution into banking and non-banking compartments. Better still, COBAC holds a right of veto. No collective proceedings may be opened in respect of a credit institution under provisional administration or under restructuring. COBAC's right of control is justified by the fact that it has powers and has more effective measures, notably the Guarantee Fund, to avoid systemic risk.
Keywords: Cohabitation; Collective proceeding; Communauté Economique et Monétaire de l'Afrique Centrale; Credit institutions; Difficulties; Difficulté; Etablissement de crédit; Mesures d'assainissement; Procédure collective; Reorganization measures; Traitement; Treatment; Établissements de crédit

Le juge-commissaire et la juridiction commerciale : contribution à l'étude d'une magistrature économique - Fageole-Maury, Ambre (Université Clermont Auvergne, 2018)
L’étude du juge-commissaire, institution importante du droit des procédures collectives, n’a pas bénéficié de recherches fondamentales, témoignant du décalage existant entre la doctrine et la pratique. Pourtant, le juge-commissaire a vu ses fonctions comme ses missions évoluer au cours des réformes législatives successives. Même si la faillite reste une défaillance ainsi qu’une faute, elle n’est plus nécessairement contraire à la morale. Désormais, échouer est devenu un aléa nécessaire qui permet à l’entreprise en difficulté de purger l’ensemble de son passif, consacrant un droit au rebond du débiteur par le législateur. Or, le législateur a offert au juge-commissaire des outils pour aider les entreprises à se restructurer. Le juge-commissaire doit dans le cadre de sa mission de surveillance, peser les intérêts contradictoires en présence. La recherche d’un équilibre entre des intérêts divergents et antagonistes a consenti à une influence politique du droit de l’entreprise en difficulté. La nécessité de déterminer une hiérarchie entre les différents intérêts s’est imposée, hiérarchie que le juge-commissaire doit faire respecter. Dans une perspective de restructuration et de sauvegarde de l’entreprise, cette étude a déterminé un nouvel intérêt : celui de l’entreprise défaillante, intérêt devant primer lorsque celle-ci mérite d’être sauvegardée. Dès lors, la fonction actuelle du juge-commissaire doit évoluer vers de nouvelles prérogatives au sein de cette magistrature économique singulière, au croisement du droit commercial, du droit des entreprises en difficulté et de la procédure civile.
Keywords: Droit de l’entreprise en difficulté; Entreprises en difficulté; France; Intérêt de l’entreprise défaillante; Juge-commissaire; Magistrature économique; Procédures collectives; Tribunal de commerce; Tribunaux de commerce

Direito concursal transfronteiriço: perspectivas para a superação da diversidade jurídica - Queiroga, Daniel Silva (Universidade Federal de Minas Gerais, 2018)
Há mais de 700 anos, o tema do direito concursal transfronteiriço está presente na agenda da doutrina e da jurisprudência. No Brasil, a ausência de normativa expressa no que diz respeito à insolvência transfronteiriça de organizações empresariais traz desafios para o direito, suscitando questionamentos sobre a competência internacional, a legitimidade ativa, o tratamento dos credores, o direito a ser aplicado, o conflito entre normas de ordem pública de diferentes Estados, entre outras possibilidades. A presente tese tem como objetivo analisar as formas atuais para a solução de problemas do direito concursal transfronteiriço, em especial, o modo como o direito brasileiro regula o assunto, bem como possível harmonização, uniformização ou unificação legislativa sobre o tema. A análise do instituto jurídico do direito concursal transfronteiriço é feita por meio do estudo de doutrinas especializadas para apresentar o estado da arte, identificando como os modelos teóricos principais (universalismo e territorialismo) e suas derivações cardeais (territorialismo cooperativo, universalismo modificado, insolvência secundária, contratualismo de carta-corporativa e regime internacional) respondem às perguntas que norteiam a tese. Em seguida, realiza-se um estudo sobre as formas de superação da diversidade jurídica e suas implicações para o direito empresarial, apontando o funcionamento dos fluxos de harmonização, uniformização ou unificação legislativa. Averigua-se, ainda, como o direito internacional (público e privado), o direito comunitário e da integração e a cooperação internacional podem contribuir para a discussão do tema. Buscam-se nas iniciativas internacionais existentes (universais, regionais, comunitários e de integração), os pontos de contato normativos que proporcionam soluções com relação à insolvência transfronteiriça, e como elas podem contribuir para a evolução do direito brasileiro. Assim, é percorrido o caminho dos tratados e iniciativas formulados entre os séculos XIV e XXI marcado pelo embate entre unidade e pluralidade, bem como entre universalismo e territorialismo. O estudo da Lei Modelo sobre Insolvência Transfronteiriça da UNCITRAL é relevante tendo em vista que esta é a disciplina legislativa mais aplicada no mundo, assim como as normas produzidas no seio do direito comunitário (UE e OHADA), que oferecem previsibilidade de conduta e a possibilidade de interpretação coordenada por tribunais comunitários. Também são discutidas as iniciativas do continente americano do fim do século XX que se encontram em desuso e em processo de revisão pela OEA, devido à evolução do direito empresarial. Também se aborda a legislação brasileira, histórica e vigente, e sua interpretação jurisprudencial para, ao final, discutir as propostas de mudança do direito concursal transfronteiriço nacional, apontando reflexões sobre a necessidade de reforma ou não da legislação brasileira. For more than 700 years, the subject of cross-border insolvency law has been on the agenda of doctrine and jurisprudence. In Brazil, the absence of express regulations regarding cross-border insolvency of business organizations brings challenges to the law, raising questions about international jurisdiction, active legitimacy, treatment of creditors, the right to be applied, conflict between public order rules of different States, among other possibilities. The purpose of this thesis is to analyze current ways of solving problems of cross-border insolvency law, in particular, how Brazilian law regulates the matter, as well as possible harmonization, uniformity or legislative unification on the subject. The analysis of the legal institute of cross-border insolvency law is done through the study of specialized doctrines to present the state of art, identifying how the main theoretical models (universalism and territorialism) and their cardinal derivations (cooperative territorialism, modified universalism, secondary insolvency, contractualism of corporate charter and international regime) answer the questions that guide the thesis. Following this, a study is carried out on ways of overcoming legal diversity and its implications for business law, pointing to the flow of harmonization, standardization or legislative unification. It also inquires how international law (public and private), community and integration law and international cooperation can contribute to the discussion of the topic. Existing international initiatives (universal, regional, community and integration) are sought in normative contact points that provide solutions regarding cross-border insolvency and how they can contribute to the evolution of Brazilian law. Thus, the way of the treaties and initiatives that were formulated between the 14th and 21st centuries marked by the struggle between unity and plurality, as well as between universalism and territorialism, is traversed. The study of UNCITRAL's Model Law on Cross-border Insolvency is relevant in view of the fact that it is the legislative measure most applied in the world, as well as the norms produced under EU law (EU and OHADA), which provide predictability of conduct and the possibility of interpretation coordinated by community courts. Furthermore, the initiatives of the American continent at the end of the twentieth century, which are in disuse and under review by the OAS due to the evolution of business law, are discussed. It also addresses the Brazilian legislation, historical and current, and its jurisprudential interpretation, in order to discuss the proposals to change national cross-border insolvency law, pointing out the need to reform or not Brazilian legislation.
Keywords: Atividade Econômica Transfronteiriça; Direito Concursal; Direito Falimentar; Direito Recuperacional; Direito empresarial; Direito internacional privado; Empresas Falência Legislação; Grupo de Sociedades; Harmonização; Insolvabilité; Insolvency; Insolvência; Insolvência Transfronteiriça; Organizações Empresariais; Sociedades comerciais; Unificação; Uniformização

La compensation en droit OHADA des entreprises en difficulté : certitudes et zones d’ombre - Maré, Youbi Bouhari (Revue de droit international et de droit comparé, 2018)
DI-fusion, le Dépôt institutionnel numérique de l'ULB, est l'outil de référencementde la production scientifique de l'ULB.L'interface de recherche DI-fusion permet de consulter les publications des chercheurs de l'ULB et les thèses qui y ont été défendues.

Insolvência transnacional: as contribuições que a lei modelo da UNCITRAL pode proporcionar para o Brasil - Becue, Sabrina Maria Fadel (Universidade de São Paulo, 2018)
O Brasil nem sempre permaneceu alheio ao debate sobre insolvência transnacional, porém desde 1973 carece de normativa específica. A lacuna da lei, no entanto, não impede que os casos cheguem ao Poder Judiciário. Nos últimos anos, o número de processos desta natureza aumentou de forma considerável e apesar de terem atingido certo consenso quanto à solução encontrada pelos tribunais, a fundamentação das decisões expõe a fragilidade do sistema e a necessidade de reforma legislativa. A prevalência da UNCITRAL entre as demais organizações internacionais e o limitado escopo e estrutura da Lei Modelo sobre Insolvência Transnacional, permitiram que este instrumento de Soft Law fosse aceito como o padrão normativo mais adequado e internacionalmente reconhecido. A Lei Modelo da UNCITRAL contribui para segurança jurídica e previsibilidade no comércio internacional, por meio da harmonização do procedimento de insolvência transnacional em países oriundos de diferentes tradições jurídicas - Civil Law e Common Law - e que estão em diferentes estágios de desenvolvimento. A harmonização se restringe a regras comuns para o reconhecimento de um processo estrangeiro, medidas de assistência e cooperação entre tribunais, sem, contudo, avançar em questões de direito material que, como sabido, são sensíveis e refletem políticas internas de cada Estado. Assim, uma das principais vantagens da Lei Modelo é promover a cooperação direta entre tribunais e com os representantes da insolvência, a fim de eliminar a dependência dos países no princípio de cortesia internacional ou concessão de exequatur aos procedimentos de homologação de sentença estrangeira ou carta rogatória. Apesar dos benefícios proporcionados pela Lei Modelo, muitos países resistem a sua adoção e, entre aqueles que a incorporaram, há diversidade na sua interpretação e aplicação, o que pode colocar em risco o objetivo de harmonização. A fratura entre o texto da lei e sua prática foi objeto da investigação. Inobstante, o Brasil poderia se beneficiar da adoção da Lei Modelo da UNCITRAL, tanto para ampliar os meios de cooperação jurídica internacional, como para promover uma solução estável aos processos transnacionais. Contudo, é preciso entender o alcance deste instrumento e, via de consequência, suas limitações enquanto norma regente, uma vez que as contribuições esperadas da Lei Modelo estão proporcionalmente vinculadas aos seus restritos escopos. A tese questiona, por fim, se existe um sistema internacional de insolvência transnacional fundado no universalismo modificado ou qual o papel que pode ser atribuído a este na solução dos processos judiciais. Brazil has not always been disconnected from the debate on transnational insolvency, but since 1973 it lacks specific regulations. The gap in legislation, however, does not prevent cases from reaching the courts. In recent years, the number of cases of this nature has increased considerably and although some consensus has been reached on the solution found by the courts, the reasoning of the rulings exposes the fragility of the system and the need for legislative reform. The predominance of UNCITRAL in relation to other international organizations and the limited scope and structure of the Model Law on Transnational Insolvency allowed this Soft Law instrument to be accepted as the most appropriate and as an internationally recognized standard of cross-border regulation. The UNCITRAL Model Law contributes to legal certainty and predictability in the international trade by harmonizing the transnational insolvency proceedings in countries from different legal systems - Civil Law and Common Law - that are at different stages of development. Legal harmonization is restricted to common rules for the recognition of a foreign proceeding, assistance and cooperation between courts, without, however, advancing in matters of substantive law which, as it is well known, are sensitive and reflect public policies of each State. Thus, one of the main advantages of the Model Law is to promote direct cooperation between courts and insolvency representatives in order to eliminate the countries' reliance on international courtesy or the granting of exequatur to the procedures for ratification of a foreign judgment or letters rogatory. Despite the benefits provided by the Model Law, many countries resist their adoption, and among those who incorporate it, there is diversity in their interpretation and application, which may jeopardize the goal of harmonization. The fracture between the law on the books and its practice was the object of this investigation. In spite of this, Brazil could benefit from the adoption of the UNCITRAL Model Law, both to expand the means of international judicial cooperation and to promote a stable solution to transnational processes. However, it is necessary to understand the scope of this instrument and, consequently, its limitations as a governing norm, since the expected contributions of the Model Law are proportionally linked to its restricted scopes. The thesis finally poses the question of whether there is an international system of transnational insolvency based on the modified universalism or the role that can be attributed to it in the resolution of legal proceedings.
Insolvabilité transfrontalière : les contributions que la loi type de la CNUDCI peut apporter au Brésil
Keywords: Cooperação internacional; Cross-border Insolvency; Direito Internacional; Insolvência; Judicial Cooperation; Modified Universalism; Sentença estrangeira

Aspects of the regulation of cross-border insolvency in South Africa - Chitimira, Howard (Obiter, 2018)
This article analyses the regulation of cross-border insolvency under the Cross-Border Insolvency Act 42 of 20001 in order to examine the adequacy of such regulation as regards to the enforcement of insolvency proceedings in South Africa and other relevant jurisdictions. To this end, the paper provides an overview analysis of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act. Moreover, where possible, the paper also provides a comparative analysis of selected aspects of the regulation and/or enforcement of insolvency proceedings under the Cross-Border Insolvency Act and those that are provided under the Insolvency Act 24 of 1936 and other related international instruments. This is done to expose the challenges and future prospects of the regulatory and enforcement framework under the Cross-Border Insolvency Act in South Africa.
Keywords: Insolvency; Regulation; South Africa

A comparative study of the effects of liquidation or business rescue proceedings on the rights of the employees of a company - Joubert, Engela Petronella (University of South Africa, 2018)
Whenever legal disciplines overlap interesting scenarios occur and differences in opinions create intellectual tension. One such interesting scenario occurs when employees’ rights are affected during a company’s liquidation or business rescue. The employees of a company are normally the last persons to find out that a company is struggling financially. They are also the only stakeholders who are in no position to negotiate their risk should the company be liquidated. It is therefore necessary to evaluate the rights given to employees during a company’s liquidation and business rescue. The fundamental ideologies of company law, insolvency law and labour law are challenged and examined to attempt a harmonizing result that respects the core of each discipline. It is crucial to determine whether an appropriate balance is struck between the interests of all the stakeholders of the company during these procedures. The aim of this thesis is to evaluate whether South Africa manages to strike this balance. If employee rights are protected whilst a company is restructured back to solvency and success, this balance will be struck. An evaluation will also be made whether employees are always better protected during business rescue than in liquidation. The study analyses employee rights in a company’s liquidation and during a company’s restructuring process. The comparative study of employee rights in liquidation and rescue is done with the jurisdictions of Australia and England – countries with similar procedures. Important conclusions show that South Africa protects employee rights during business rescue procedures the best. An appropriate balance is indeed struck between the interests of all stakeholders of a company during business rescue procedures and employees are most of the time better off after a restructuring than in a liquidation. Should the recommendations for law reform be implemented in our legislation, South Africa will overcome the few obstacles currently in its way to be seen as a world leader where employee rights are concerned in liquidation proceedings as well as business rescue.
Keywords: Australia; Bankruptcy; Business rescue; Corporate reorganizations; Employee rights; Employment contract; Great Britain; Liquidation; Ranking of claims; South Africa

La subasta concursal - Huerta García, Rafael (Universitat de Barcelona, 2018)
La subasta judicial ha sido objeto de una profunda transformación a raíz de la entrada en vigor de la Ley 19/2015, que estableció como principal novedad la obligatoriedad de publicación en el BOE y Portal de Subastas del BOE de todas las subastas judiciales y notariales convocadas a partir del 15 de octubre de 2015, eliminando el concepto de puja presencial existente. Por lo que respecta a la subasta concursal, tras el análisis de 4804 lotes concursales subastados por los Juzgados Mercantiles en el año 2016, se ha evidenciado la existencia de tres sistemas de liquidación diferenciados (sistema de Tipo libre, Tipo especial y Tipo LEC), que adaptan en mayor o menor medida las reglas generales de la subasta judicial de la LEC (arts. 643 y ss.) en función del Plan de Liquidación aprobado, circunstancia que produce una alteración en el Porcentaje de lotes desiertos (PLD), Tasa de Recuperación del Pasivo Insatisfecho (TRPI) y Tasa de Eficacia de la Subasta Judicial (TESJ). Resulta necesario por tanto conocer, los aspectos positivos y negativos de cada sistema de liquidación de subasta concursal, para la elaboración de un modelo de subasta concursal eficaz, objetivo último del presente trabajo.
URI: https://www.tdx.cat/handle/10803/665004
Keywords: Civil law; Courts; Derecho mercantil; Dret civil; Dret mercantil; Econòmiques i Socials; Judicial auctions; Merchant law; Subastas judiciales; Subhastes judicials; Tribunales; Tribunals

L'implication du salarié dans la prévention et le traitement des difficultés des entreprises dans l'espace OHADA : le cas du Cameroun - Kouamo, Darly Russel (Université de Nantes, 2018)
La recherche des solutions pour prévenir ou éradiquer les difficultés de l’entreprise passe par l’articulation de diverses interventions d’acteurs. En ce sens, le droit de l’Organisation pour l’Harmonisation en Afrique du droit des Affaires (OHADA), applicable au Cameroun, a doté le débiteur, les créanciers et les organes judiciaires de nombreuses prérogatives. Cependant, le salarié semble être privé de réelles possibilitésd’anticiper ou d’influencer le processus, alors qu’il est au plus fort degré intéressé par la pérennisation de l’entreprise. Le sentiment d’exclusion du processus pourrait démotiver le salarié et entacher ses performances au sein de l’entreprise ; alors que son intégration dans la conception et la prise des décisions serait susceptible de développer un sentiment de solidarité d’une part avec les dirigeants, d’autre part avec les autres salariés. Ainsi, lorsque l’entreprise connaît des difficultés, le dialogue qui s’ouvre à ceteffet doit rassembler toutes les parties prenantes. Il faudrait fédérer toutes les énergies qui s’activent quotidiennement au service de l’entreprise. La présente recherche entend proposer une approche d’implémentation du dialogue social aussi bien dans la gestion quotidienne de l’entreprise que dans la résolution des crises ; en somme, une réelle implication du salarié dans le processus décisionnel.
Keywords: Entreprises en difficulté; Négociations collectives; Organisation pour l'harmonisation en Afrique du droit des affaires; Participation à la gestion; Personnel; Procédures collectives préventives

Les sûretés à l'épreuve de la réforme OHADA des procédures collectives du 10 septembre 2015 - Akono Adam, Ramsès (Revue de l'ERSUMA, 2018)
La présente étude dégage deux tendances majeures. D'une part les sûreés sont fragilisées dans l'AUPC révisé parce qu'elles ne peuvent plus être réalisées librement par leurs titulaires à compter de l'ouverture de la procédure collective. La fragilisation des sûretés personnelles et réelles s'explique par des raisons de recherche de rdressement de l'entreprise débitrice et de traitement collectif des créanciers antérieurs. D'aute part, certaines sûretés (exclusives) résistent aux assauts de la discipline collective. Mais cette survie paraît relative, parce que leurs titulaires ne sortent pas indemnes des sujétions imposées par l'ouverture d'une procédure collective. C'est dure qu'on chasse le droit des procédures collectives, il revient au galop.
Keywords: Procédures collectives; Réforme OHADA; Sûretés

Les procédures collectives des établissements de crédits dans l'espace OHADA - Gueye, Ramata (Université Cheikh Anta Diop, 2018)

Le traitement des difficultés de l’entreprise pour assurer sa survie : étude comparative - Harrat, Mohammed (Université d'Oran 2 Mohamed Ben Ahmed, 2018)
Lorsqu’un débiteur non commerçant ne peut faire face à ses engagements, il est dans l’état de déconfiture, alors que s’il est commerçant, sont applicable des procédures collectives prévues par le droit commercial. Les difficultés de l’entreprise peuvent être traitées soit par la prévention et le traitement non judiciaire, comme la prévention par l’information économique et la prévention par l’information comptable et la prévention par l’alerte des dirigeants et le traitement administratif et conventionnel, soit par le traitement judiciaire, qui englobe la procédure de sauvegarde et le règlement et redressement judiciaires d’une part, et la faillite et la liquidation judiciaire d’autre part. When a non-trading debtor can not meet his obligations, he is in a state of collapse, whereas if he is a merchant, collective procedures provided for by commercial law are applicable. The difficulties of the company can be treated either by the prevention and the non-judicial treatment, as the prevention by the economic information and the prevention by the accounting information and the prevention by the alert of the leaders and the administrative and conventional treatment or by judicial treatment, which includes the procedure of safeguard and settlement and judicial reorganization on one hand, and bankruptcy and judicial liquidation on the other hand. عندما يتعذر على المدين الغير تاجر الوفاء بتعهداته، يكون في حالة إعسار في حين أنه إذا كان تاجرا، فتطبق الإجراءات الجماعية المنصوص عليها في القانون التجاري. ويمكن معالجة الصعوبات التي تواجهها الشركة إما بالوقاية والمعالجة غير القضائية، مثل الوقاية عن طريق المعلومات الاقتصادية والوقاية بواسطة المعلومات المحاسبية والوقاية عن طريق تنبيه المسيرين والمعالجة الإدارية والاتااقية أو المعالجة القضائية، التي تشمل إجراءات الانقاذ والتسوية والتقويم القضائي من جهة، والإفلاس والتصاية القضائية من جهة أخرى
Keywords: Alerte; Bankruptcy; Companies difficulties; Difficultés des entreprises; Faillite; Judicial settlement; Prevention; Prévention; Règlement judiciaire; Sauvegarde; Saving; Warning

El poder de decisión en las sociedades en situación de insolvencia y de déficit patrimonial la incidencia de los expedientes preconcursales - Vázquez Cueto, José Carlos (Sociedades y concurso, 2018)
Accepted: 2024-01-18T12:04:33Z Publisher: Aranzadi